Used territory, social analysis category. From Milton Santos to Maria Adélia Aparecida de Souza - Costa, Everaldo Batista (2024)
With this editorial from number. 15, vol. 8 of PatryTer – Revista Latinoamericana y Caribena de Geografia y Humanidades – it is intended to recapture, in a synthetic way, the debate inaugurated by Milton Santos on the territory used, a category of social analysis, to demonstrate that, in more than sixty years (1962- 2024) dedicated to Geography, Maria Adélia de Souza, from Brazil has contributed to it contemporary discussion of the topic. This is demonstrated in its consolidated scientific production, fully justifying the tribute dedicated to Dr. Adélia de Souza in this issue of the magazine.